Nonunion fractures, mesenchymal stem cells and bone tissue engineering. Issue 9 (2nd May 2018) - Toosi, Shirin; Behravan, Nima; Behravan, Javad
Abstract: Depending on the duration of healing process, 5–10% of bone fractures may result in either nonunion or delayed union. Because nonunions remain a clinically important problem, there is interest in the utilization of tissue engineering strategies to augment bone fracture repair. Three basic biologic elements that are required for bone regeneration include cells, extracellular matrix scaffolds and biological adjuvants for growth, differentiation and angiogenesis. Mesenchymal stem cells (MSCs) are capable to differentiate into various types of the cells including chondrocytes, myoblasts, osteoblasts, and adipocytes. Due to their potential for multilineage differentiation, MSCs are considered important contributors in bone tissue engineering research. In this review we highlight the progress in the application of biomaterials, stem cells and tissue engineering in promoting nonunion bone fracture healing. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A:2551–2561, 2018.